'The power of attraction': the staging of Wilde and his contemporaries at the St James's Theatre, 1892–1895 - Sutherland, Lucie (Cambridge University Press, 2015)
The actor-manager system remained pivotal to West End production throughout the later nineteenth century. Focusing on one actor-manager, George Alexander, and using records of his expenditure on productions during the early 1890s, Lucie Sutherland demonstrates how financial data can be used to examine evolving relationships between industry leaders and dramatic authors in this era. She argues that this kind of evidence demonstrates not only the fiscal dimension to such relationships – level of investment per production, percentage of royalties paid – but also that the data may be analyzed to ascertain the responsiveness of an actor-manager to income generated. Here, significant attention is paid to box-office revenue and expenditure for the first productions of Lady Windermere's Fan and The Importance of Being Earnest, exploring the income Alexander achieved by staging Wilde's drama prior to the arrest and trials of 1895. The use of quantitative data allows for close scrutiny of the work undertaken by prominent figures in the professional theatre; familiar narratives can be contested and endorsed through engagement with this type of material. Lucie Sutherland is a Teaching Associate in Drama and Performance at the University of Nottingham. She has written on aspects of nineteenth- and twentieth-century British theatre, including regional performance cultures and the impact of increasing professional regulation (for example the emergence of an actors' union) upon commercial theatre. She is currently completing a critical biography of Alexander